Enhancing oral competence: Evidence-based strategies for developing foreign language speaking skills in Deaf and Hard-of-Hearing (DHH) learners - Izabela Olszak; Aleksandra Borowicz (PLoS ONE, 2026)
This study examines evidence-based pedagogical strategies aimed at enhancing communication competence, with a particular focus on foreign language speaking skills, among Deaf and Hard of Hearing (DHH) students at the primary education level. Acknowledging the distinct linguistic, cognitive, and communicative characteristics of DHH learners, the research addresses the central question: Which instructional techniques most effectively promote the development of speaking and broader communicative abilities in this population? Employing a qualitative research design, the study engaged 55 primary-level DHH students and utilized classroom observations, student questionnaires, and semi-structured interviews with teachers and educational specialists, thereby adopting a multi-perspective methodological framework that enables the triangulation of learner, classroom and professional perspectives. The findings underscore the efficacy of multimodal and visually enriched teaching approaches, the value of differentiated, learner-centered instruction, and the importance of collaborative learning environments in supporting oral foreign language development. The research provides empirical insights into the design of inclusive and responsive language education practices for DHH learners, including those relevant to foreign language speaking skills, drawing on triangulated qualitative evidence from multiple educational stakeholders, contributing to the advancement of both academic achievement and communicative competence in diverse classroom settings.